A Defined Antigen Skin Test That Enables Implementation of BCG Vaccination for Control of Bovine Tuberculosis: Proof of Concept - Srinivasan, Sreenidhi; Subramanian, Saraswathi; Shankar Balakrishnan, Sai; Ramaiyan Selvaraju, Kathiravan; Manomohan, Vandana; Selladurai, Suganya; Jothivelu, Monika; Kandasamy, Srinivasan; Gopal, Dhinakar Raj; Kathaperumal, Kumanan; Conlan, Andrew J. K.; Veerasami, Maroudam; et al. (Frontiers in Veterinary Science, 2020)
In most low- and middle-income countries (LMICs), bovine tuberculosis (bTB) remains endemic due to the absence of control programs. This is because successful bTB control and eradication programs have relied on test-and-slaughter strategies that are socioeconomically unfeasible in LMICs. While Bacillus Calmette–Guérin (BCG) vaccine-induced protection for cattle has long been documented in experimental and field trials, its use in control programs has been precluded by the inability to differentiate BCG-vaccinated from naturally infected animals using the OIE-prescribed purified protein derivative (PPD)-based tuberculin skin tests. In the current study, the diagnostic specificity and capability for differentiating infected from vaccinated animals (DIVA) of a novel defined antigen skin test (DST) in BCG-vaccinated (Bos taurus ssp. taurus x B. t. ssp. indicus) calves were compared with the performance of traditional PPD-tuberculin in both the skin test and in vitro interferon-gamma release assay (IGRA). The IFN-γ production from whole blood cells stimulated with both PPDs increased significantly from the 0 week baseline levels, while DST induced no measurable IFN-γ production in BCG-vaccinated calves. None of the 15 BCG-vaccinated calves were reactive with the DST skin test (100% specificity; one-tailed lower 95% CI: 82). In contrast, 10 of 15 BCG-vaccinated calves were classified as reactors with the PPD-based single intradermal test (SIT) (specificity in vaccinated animals = 33%; 95% CI: 12, 62). Taken together, the results provide strong evidence that the DST is highly specific and enables DIVA capability in both skin and IGRA assay format, thereby enabling the implementation of BCG vaccine-based bTB control, particularly in settings where test and slaughter remain unfeasible.